Standard value of ultrasound elastography using acoustic radiation force impulse imaging (ARFI) in healthy liver tissue of children and adolescents. - Eiler, J.; Kleinholdermann, U.; Albers, D.; Dahms, J.; Hermann, F.; Behrens, C.; Luedemann, M.; Klingmueller, V.; Alzen, G. F. P. (Ultraschall in der Medizin - European Journal of Ultrasound, 2012)
Purpose: Ultrasound elastography by acoustic radiation force impulse imaging (ARFI) is used in adults for non invasive measurement of liver stiffness, indicating liver diseases like fibrosis. To establish ARFI in children and adolescents we determined standard values of healthy liver tissue and analysed potentially influencing factors.Materials and Methods: 132 patients between 0 and 17 years old were measured using ARFI. None of them had any liver disease or any other disease that could affect the liver secondarily. All patients had a normal ultrasound scan, a normal BMI and normal liver function tests. The mean value of all ARFI measurements was calculated and potentially influencing factors were analysed.Results: The mean value of all ARFI elastography measurements was 1.16 m/sec (SD ± 0.14 m/sec). Neither age (p = 0.533) nor depth of measurement (p = 0.066) had no significant influence on ARFI values, whereas a significant effect of gender was found with lower ARFI values in females (p = 0.025), however, there was no significant interaction between age groups (before or after puberty) and gender (p = 0.276). There was an interlobar difference with lower values in the right liver lobe compared to the left (p = 0.036) and with a significantly lower variance (p < 0.001). Consistend values were measured by different examiners (p = 0.108), however, the inter examiner variance deviated significantly (p < 0.001).Conclusion: ARFI elastography is a reliable method to measure liver stiffness in children and adolescents. In relation to studies which analyse liver diseases, the standard value of 1.16 m/sec (± 0.14 m/sec) allows a differentiation of healthy versus pathological liver tissue.
Keywords: acoustic radiation force impulse imaging elastography; liver stiffness; children; standard value; healthy subjects